THE EFFECT OF INTERACTIVE DIGITAL STORYTELLING THROUGH PICTURE SERIES ON STUDENTS’ SPEAKING SKILLS - Galuh Rofanda; Bradiansyah T Suryanto (IJEE (Indonesian Journal of English Education), 2026)
Speaking plays a crucial role in English language acquisition as it allows students to express meaning in real-life situations. Despite its significance, many junior high school students struggle to develop speaking proficiency due to restricted vocabulary, limited self-assurance, feelings of anxiety, and lack of opportunities for authentic communication. This research sought to investigate how interactive digital storytelling combined with picture sequences affects students' speaking abilities. The study employed a quasi-experimental approach utilizing pre-test and post-test assessments with both experimental and control groups. A total of sixty Grade 8 students from a public junior high school in East Java took part, randomly assigned to two groups. The experimental group was taught using interactive digital storytelling supplemented with picture series across six sessions, whereas the control group received traditional classroom instruction. Data gathering involved speaking performance evaluations measuring four criteria: fluency, vocabulary, pronunciation, and content organization. Two separate raters scored the students' performances, and inter-rater reliability calculated through Cohen's Kappa reached 0.87, demonstrating strong consistency between evaluators. Statistical analysis using independent-sample t-test revealed a statistically significant difference between the groups (t(58) = 14.57, p < 0.001), with the experimental group exhibiting notably greater progress. The effect size (Cohen's d = 3.76) reflects an extremely substantial influence. The results indicate that combining narrative elements, visual support, and digital interactive features can notably enhance speaking competence and increase student involvement in EFL learning environments.